Design And Development of Population Service Administration System With Pieces Method In Kemiri Village Head Office Banten - Rosdiana, Rosdiana; Padeli, Padeli; Handayni, Revi Sajidah Sri; Alfian, Rifky (ADI Journal on Recent Innovation, 2019)
The public service administration system at the government offices of the Kemiri village office in the Kemiri District currently does not have a computerized and integrated system. Because the system runs, residents who submit letters for administrative completeness, still use the Ms.Word / Ms.Excel application. of course has many weaknesses including human error, not neat in file storage, resulting in the lengthy process of searching and making a cover letter and required reports. The analytical method used in this study is to use PIECES (Performance, Informance, Economy, Control, Efficiency, Service) analysis, the design of the model uses UML (Unified Modeling Language). The results of this study are web-based letter information systems at the Office of the Village Chief of Kemiri that can accessed using a local computer browser. Thus the information letter needed by the Kemiri Village community and more effective and efficient in making the letter.